Profile of Intravenous Admixture Drugs in Newborn Patients at Dr. Moewardi General Hospital Surakarta - Inesya Febrianing Rizki; Zakky Cholisoh (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
Intravenous admixtures are sterile solutions prepared by mixing one or more different drugs with a suitable solvent and given to patients via the intravenous route. One of the factors causing contamination of the intravenous preparation mixture is an error in the aseptic technique during the preparation phase. Errors in aseptic techniques can cause infection. Newborns (neonates) are children under the age of 28 days. During 28 days of birth, have the highest risk of dying. The rate of potentialÂ adverse drug events (ADE)Â is three times higher in children than adults and substantially higher in neonates receiving intensive care. Intravenous admixture therapy, often performed in general wards, is highly susceptible to bacterial contamination which can result from aseptic technique errors. Bacterial contamination in intravenous preparations can cause infection which can trigger septic shock to death. The purpose of this study was to evaluate the suitability of the mixing process and the process of administering intravenous admixture drugs to infant patients. This study was conducted on infant or neonatal patients who were hospitalized in general wards and special intensive wards for babies in hospitals. Dr. Moewardi Surakarta. The research took place from February to March 2020 and was carried out using a prospective observational method. The inclusion criteria for this study were patients receiving parenteral drug therapy with complete medical records. Analysis of drug miscibility/insolubility was carried out using Handbook an Injectable Drugs edition 17 as the main reference and ASHP Drug information handbook 2021 edition. The results of this study, the percentage of solubility of injectable drugs that dissolved was 44 times administration (36.7%). For the administration of insoluble drugs 3 times (2.5%) and 73 (60.8%) administrations there was no information regarding the solubility of the drugs given. The study concludes that although there is incompatibility potential information references, at the direct observation was no incompatibility found. The administration of the two potentially insoluble drugs was carried out with different syringe containers.